KEPEMIMPINAN TRANSFORMASIONAL DAN EFEKTIFITAS ORGANISASI DI MADRASAH IBTIDAIYAH ZAINUL YASIN KOTA PROBOLINGGO - Khosiah, Nur; Sofiani Rizkillah, Nizrina (LPPM STAI Muhammadiyah Probolinggo, 2024)
understands each other, complements each other, and provides freedom of opinion for the sake of mutual progress, of course it will make a company or institution a second home for its citizens, but if a leader in a company or an institution not playing a good role will certainly be a setback and destruction for the institution. Transformational leadership is the most common leadership model chosen by company or institutional leaders. This research uses qualitative methods and literature studies, the aim of this research is to gain a better understanding of the concept of transformational leadership and organizational effectiveness at Madrasah Ibtidaiyah, Probolinggo City. And the result is that the Principal always motivates teachers to improve their performance, including holding educational seminars, freedom of opinion for the sake of school progress, collaborating with teachers so that students become better and the school also progresses.